Replication of "Solar Eclipses and the Origins of Critical Thinking and Complexity" - Marie Connolly; Oumar Djamaldiev; Andrei Munteanu (Institute for Replication (I4R), 2024)
Overall, the results of this study are replicable using the clean dataset provided by the authors. However, the process of transforming the raw data into this clean dataset is at times unclear, and certain essential codes are missing from the replication materials, which may hinder complete replication. Despite these challenges, the paper's findings remain robust to a small number of robustness checks that we conducted, providing confidence in the reliability and stability of the results. Moving forward, efforts to enhance transparency in data transformation steps and inclusion of all necessary codes would facilitate more seamless replication and validation of the study's outcomes.
Keywords: 330